Religiosity, Knowledge, and Satisfaction on Students' Saving Decisions: A Moderating Effect of Interest in Islamic Banks - Aunika, Vita; Sukardi, Budi; Adib Susilo (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
This study aims to determine the effect of religiosity, knowledge, and satisfaction on saving decisions in Islamic banks with interest as an intervening variable with a case study of Greater Solo students. This study employed quantitative methods using primary data. The sampling technique used was simple random sampling. Data collection was done by distributing questionnaires via Google Forms. The sample size was 200 students from Solo Raya. This study used the SMART-PLS analysis tool with the Partial Least Square Structure Equation Model (PLS-SEM) analysis model. The results of SEM-PLS research prove that religiosity and satisfaction significantly affect interest in saving in Islamic banks. Knowledge has no significant effect on interest in saving in Islamic banks. Interest, religiosity, and satisfaction significantly affect saving decisions at Islamic banks. Interest has a significant effect in mediating religiosity and satisfaction on saving decisions at Islamic banks. Meanwhile, interest does not affect the mediating effect of knowledge on saving decisions in Islamic banks. The research has implications for proving the low level of student knowledge regarding sharia financial literacy, by encouraging student awareness regarding sharia financial literacy in sharia financial practices. Increasing sharia financial literacy will contribute to improving the sharia economy.